The coinage of Herod Antipas: a study and die classification of the earliest coins of Galilee - Kogon, Aaron J. (Ancient Judaism and early Christianity, 2018)
Intro -- ‎Contents -- ‎Foreword -- ‎Preface -- ‎Acknowledgements -- ‎List of Figures and Tables -- ‎Figures -- ‎Tables -- ‎Abbreviations -- ‎General -- ‎Ancient Works -- ‎Talmudic Tractates -- ‎Chapter 1. Introduction -- ‎1.1. Documentary Sources for Antipas -- ‎1.2. Herod Antipas' Biography -- ‎1.3. Economy of Galilee -- ‎Chapter 2. The Coins -- ‎2.1. Research on the Coins of Antipas -- ‎2.2. Herod Antipas' Numismatic Corpus -- ‎2.3. Attribution of Type No. 1 -- ‎2.4. Division of the Coins into Groups -- ‎Chapter 3. Denominations and Metrologies -- ‎3.1. Series A (Coin No. 1) -- ‎3.2. Series B-F -- ‎Chapter 4. Chronology -- ‎4.1. Denoting Dates -- ‎4.2. Reasons for Minting Each Series -- ‎4.3. Misreading of Dates in the Literature -- ‎Chapter 5. The Mints -- ‎5.1. Series A (Coin No. 1) -- ‎5.2. Series B-F and the Foundation of Tiberias -- ‎Chapter 6. Dies and Minting -- ‎6.1. Die Cutting -- ‎6.2. Die Study -- ‎6.3. Relative Quantities of Types -- ‎6.4. Die Axes -- ‎6.5. Minting Process -- ‎6.6. Composition -- ‎Chapter 7. The Inscriptions -- ‎7.1. The Name of Herod Antipas -- ‎7.2. HPW / TeTPA[PX?]HC (Herod the Tetrarch) -- ‎7.3. HP‭ΩΔ‬OY TETPaPXOY (Of Herod the Tetrarch) and Variants -- ‎7.4. HP‭ΩΔ‬HC TETPaPXHC (Herod the Tetrarch) and Variants -- ‎7.5. TIBEPIaC (Tiberias) and Variants -- ‎7.6. ‭Γ‬aI‭Ω‬ KaICAPI ‭Γ‬EPMaNIK‭Ω‬ (To Gaius Caesar Germanicus) -- ‎7.7. Letter Forms -- ‎Chapter 8. The Iconography -- ‎8.1. Aniconism -- ‎8.2. Palm Tree -- ‎8.3. Grain (?) -- ‎8.4. Wreath -- ‎8.5. Reed -- ‎8.6. Palm Branch -- ‎8.7. Cluster of Dates -- ‎8.8. Iconography of Type No. 14 -- ‎Chapter 9. Geographical Distribution -- ‎9.1. Gaulanitis -- ‎9.2. Upper Galilee -- ‎9.3. Lower Galilee -- ‎9.4. Decapolis -- ‎9.5. Judaea -- ‎9.6. Samaria -- ‎9.7. Outside Palestine -- ‎9.8. Summary and Analysis of the Provenanced Finds